A new triple sum combinatorial identity - Joseph Sinyor; Akalu Tefera (International Journal of Mathematics and Mathematical Sciences)
We prove a new triple sum combinatorial identity derived from rp(x,y,z)=(x+y−z)p−(xp+yp−zp), extending a previous result by Sinyor et al.